Impact of the circular economy on quality of life – A systematic literature review: A Systematic review of the literature - Sekulić, Milena; Stojanović, Vladimir; Pantelić, Milana; Nađ, Imre (Geographica Pannonica, 2022)
The circular economy (CE) is a multidisciplinary approach focused on achieving the sustainability of the whole society. This review aims to reveal the potential impact of the circular economy on quality of life. This systematic review analyzes studies dealing with the concept of circular economy and quality of life. The methodology process included a keyword search and three selection steps. A total of 39 studies were included in the analysis. We define four topics that emerged from the literature review i) urban sustainable development; ii) waste management; iii) material production and iv) human well-being. All these topics emerged in the literature dealing with issues of circular economy and its impact on the quality of life. We assume that it is implied that every step towards circular economy contributes to the life quality, but there is an evident lack of studies that measure that impact. In Serbia, a small number of researchers were involved in this topic, although it represents one step towards the objective of improving the state of the environment. This review of the literature should serve as a starting point for future research.